2020
DOI: 10.3390/brainsci10110819
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study Testing Autonomic Reactivity to Pain in Women with Sensory Over-Responsiveness

Abstract: Background: Difficulty modulating sensory input related to multi-sensory integration dysfunction, specifically the sensory over-responsive (SOR) type, is associated with psychological distress and hyperalgesia in children and adults. Scares reports suggest atypical autonomic nervous system (ANS) reactivity to innocuous sensory stimuli in children with SOR. Thus, the ANS may contribute to sensory stimuli responses and psychological distress. This exploratory study aimed to characterize the ANS reactivity to sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, the study was limited to a sample of 20 adults who were classified as having extreme scores in one of the four sensory processing patterns. In the study by Bar-Shalita et al (2020), nine women classified as having sensory over-responsiveness exhibited a smaller change in parasympathetic nervous system activity during a pain elicitation task, compared to nine women who were not overly responsive to sensory stimuli. The researchers concluded that sensory over-responsiveness may be underpinned by inefficient regulation of autonomic activity (Bar-Shalita et al, 2020).…”
Section: Psychophysiological Correlates Of Sensory Processing Patternsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the study was limited to a sample of 20 adults who were classified as having extreme scores in one of the four sensory processing patterns. In the study by Bar-Shalita et al (2020), nine women classified as having sensory over-responsiveness exhibited a smaller change in parasympathetic nervous system activity during a pain elicitation task, compared to nine women who were not overly responsive to sensory stimuli. The researchers concluded that sensory over-responsiveness may be underpinned by inefficient regulation of autonomic activity (Bar-Shalita et al, 2020).…”
Section: Psychophysiological Correlates Of Sensory Processing Patternsmentioning
confidence: 97%
“…Sensory processing fundamentally shapes how individuals experience the world and affects engagement in daily occupations (Koenig and Rudney, 2010). A growing body of research with children (Christensen et al, 2020; Gomez et al, 2017) and adults (Bar-Shalita et al, 2020; Brown et al, 2001) suggests that sensory processing differences may be linked to patterns of autonomic nervous system (ANS) activity. This research has primarily used biomarkers of either the sympathetic or parasympathetic branches of the ANS; however, recent recommendations suggest that studies should concurrently measure both systems (Christensen et al, 2020; Gomez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, testing daily pain revealed enhanced pain sensitivity in individuals with SOR compared with normoresponsive people [5,6]. Furthermore, utilizing experimental pain via psychophysical testing indicated hyperalgesia (amplified pain intensity) and lingering pain sensation [7][8][9][10], as well as altered physiological reactivity [11,12], which may suggest compromised endogenous pain modulation in otherwise healthy children and adults with SOR [10,13]. Moreover, SOR has been widely reported to be associated with psychological distress and emotionality, e.g., [14][15][16], and both are also considered to be factors in phenotyping pain [17].…”
Section: Introductionmentioning
confidence: 97%
“…Individuals can feel overwhelmed by sensory bombardment; therefore, they may need to escape from their environment to ‘be recharged’. This condition could result in an increased tendency to develop stress, anxiety and depression symptoms (Abernethy, 2010; Bar-Shalita et al, 2020; Benham, 2006; Engel-Yeger and Shochat, 2012; Kinnealey and Fuiek, 1999; Kinnealey et al, 1995, 2011), whereas people with sensory sensitivity can be as healthy as those who are not sensitive when in low-stress conditions. It is therefore important to determine the sensory sensitivity of adults (Ayres, 1972; Benham, 2006).…”
Section: Introductionmentioning
confidence: 99%